Minimum wages : measures and industry effects - Peterson, John M. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1981)
This study proposes to develop a new measure of the minimum- wage variable and to apply it to industry data where man- hour measures are available. Chapter 2 begins with description and criticism of the present measures used in time series regression studies. Chapter 3 proposes a new minimum wage measure, called the relative minimum wage impact.
Includes bibliographical references.
ahz 13/03/2019
Loans
Keywords: Minimum wage